اتجاھات الطلبة نحو الغش الاكادیمي - أ.م.د.كریم عبد ساجر م.د. فوزیة محمد حسین أ.م.مالیة محمد فرحان (College of Education for Women, 2019)
The Research aims to understand Student's attitudes towards Academic Cheating in the Technical College -Baghdad. The study was made on a sample of (88) students in the fourth (final) year who were randomly selected from the every scientific department in the college. The researchers prepared academic cheating a questionnaire. The research results showed that. The results showed that there is a strong trend among the students to reject the cheating phenomenon. ( 72.72%) of the specimen groups do not see that there is a justification in cheating, on the other hand the results determined the means and reasons for the cheating by the students and the negative outcome of that phenomenon.